Learning style preferences of logistics learners - Lambert, K. (South African Journal of Higher Education, 2019)
The VARK model categorises learners as visual (V), aural (A), read/write (R) and kinaesthetic (K). The VARK learning style preference of logistics students has not previously been evaluated. In this study the learning style preferences of logistics final year Diploma students from Tshwane University of Technology were therefore determined. Eighty questionnaires were distributed with 78 being received back, representing a response rate of 97.5 per cent. Of the 78 received back, two could not be used as they were not completed in full, giving 97.4 per cent of useful questionnaires (76 from 78). The dominant learning preference amongst the Logistics III students was a K (kinaesthetic) learning preference (21 out of 76, or 27.6%), followed by R (read/write) learning preference (15 out of 76, or 19.7%). VARK learning preference was third with 10 of 76 (13.2%). In the study 56.6 per cent and 43.4 per cent of the learners preferred unimodal learning and multimodal learning styles respectively.